Gender Representation in the Gwangju Democracy Movement (Gwangju Uprising): A Discussion of the Films A Taxi Driver (2017) and A Petal (1996) - Jorge, Marina Soler; Andrade, Júlia Santos (Global Journal of Cultural Studies, 2024)
Between 18 and 27 May 1980, South Korea witnessed what became known as the Gwangju Democracy Movement or the Gwangju Uprising. On this occasion, South Korean citizens, especially young people belonging to the student movement, took to the streets of the city demanding democracy and were violently repressed by the government, resulting in a death toll that is still unknown today. This paper aims to analyze two films that deal with the Gwangju Democracy Movement, A Taxi Driver (Hun Jang, 2017) and A Petal (Jang Sun-woo, 1996), focusing mainly on gender issues as the two films differ in this regard: A Taxi Driver has a story centered on male characters and brotherhood between men, while A Petal has as its protagonist a girl who is the victim of various forms of violence as a result of the Gwangju Uprising. We will try to show that the films construct a masculinist representation of the Gwangju Democracy Movement, even when they use female characters. The methodology used is based on Pierre Sorlin's sociology of cinema.